Electrospraying as a suitable method for nanoencapsulation of the hydrophilic bioactive dihydrochalcone, aspalathin. (15th March 2019) - Human, Chantelle; De Beer, Dalene; Van Der Rijst, Marieta; Aucamp, Marique; Joubert, Elizabeth
Highlights: Semi-purified aspalathin fraction (GRAF) was successfully nanoencapsulated. GRAF nanoencapsulation can be achieved with various polymers and methods. Electrospraying with synthetic polymers produce nanoparticles with best properties. Sustained release confirmed for GRAF-Eudragit S100 nanoparticles. Abstract: The bioactive hydrophilic dihydrochalcone, aspalathin, has poor stability and bioavailability hampering its use in functional food ingredients with standardised aspalathin content. The aim of the study was to produce nanoparticles with controlled release to overcome these obstacles. Nanoencapsulation was investigated using both natural (chitosan and lecithin) and synthetic (poly(lactide- co -glycolide) and Eudragit S100® (ES100)) polymers by suitable conventional methods and electrospraying for all polymers. All polymer-method combinations produced particles smaller than 1.1 µm. Electrospraying produced more favourable results than conventional methods for the synthetic polymers, resulting in spherical particles with higher (p < 0.05) encapsulation efficiencies (>50%) and loading capacities (>10%). Opposite trends were observed for natural polymers. An in vitro release study revealed biphasic aspalathin release profiles at pH 7.4 with ES100 electrosprayed nanoparticles having the slowest ( p  < 0.05) release rate (1.67 h −1 ). Overall, ES100 electrosprayed nanoparticles showed the most favourable combination of parameters.